Tissue distribution of ethanol after intraprostatic injection using a porous needle - Eubank, Megan N.; Švihra, Ján; DiBona, Kevin C.; Sommers, Matthew; Oe, Tyler; Strnádel, Ján; Miklušica, Juraj; Szépe, Peter; Marcinek, Juraj; King, Benjamin J.; Plante, Mark K.; Ľupták, Ján; et al. (Frontiers in Oncology, 2023)
Purpose: To develop a safe and precise method for intraprostatic injection and to establish correlation between the volume of the injectate and the volume of infiltrated area of the prostate. Materials and Methods: We performed intraprostatic injection of 96% ethanol using a needle which has a segment of its wall made of capillary membrane with hundreds of pores in an acute and chronic canine experiment, in heart-beating cadaveric organ donors, and in a xenograft model of human prostate cancer. Whole mount tissue sections were used for three-dimensional reconstruction of the necrotic lesions and calculation of their volumes. Results: The ethanol injection resulted in oval shaped lesions of well-delineated coagulative necrosis. In both healthy human and canine prostates, the prostatic pseudocapsule and neurovascular bundle remained intact without evidence of disruption. There was a linear correlation between administered volume of ethanol and the volume of necrotic lesion. Regression analysis showed strong correlation in the acute canine experiments and in experiments performed on xenografts of human prostate cancer. A formula was calculated for each experiment to estimate the relationship between the injected volume and the volume of infiltrated prostate tissue area. Conclusions: Intraprostatic injection using a porous needle allows for effective and predictable tissue distribution of the injectate in the prostate. Through varying the volume of the agent injected and use of needles with a different length of the porous segment, the volume of infiltrated tissue could be adjusted allowing for targeted focal treatment.